2012
DOI: 10.1128/jvi.00166-12
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus T-Cell Ligand Sequences Shared with Other Flaviviruses: a Multitude of Variant Sequences as Potential Altered Peptide Ligands

Abstract: West Nile virus (WNV), a member of the genus Flavivirus, is a mosquito-borne RNA pathogen closely related to numerous other flaviviruses of the Japanese encephalitis (JE) group, and to a lesser degree to Dengue virus (DENV), Yellow fever virus (YFV), and several other flaviviruses of about 70 different species (5, 18). The genome is a positive-sense, single-stranded RNA of approximately 10,293 nucleotides encoding a polyprotein of approximately 3,430 amino acids (aa) that is cleaved to produce three structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
2
10
0
Order By: Relevance
“…The number of epitopes found on HLA class II TgM outnumbered the HLA class I counterpart, which is consistent with other studies using the same TgM animal model and similar immunization strategies [53], [67]. The combination of immunization strategy (with peptide pool), the difference in topology between HLA class I and II molecules and the HLA class I epitope processing mechanism [68] might explain the reasons for the paucity of HLA class I epitopes identified in our study and, thus, revealing to be a caveat for identification of HLA class I restricted epitopes.…”
Section: Discussionsupporting
confidence: 91%
“…The number of epitopes found on HLA class II TgM outnumbered the HLA class I counterpart, which is consistent with other studies using the same TgM animal model and similar immunization strategies [53], [67]. The combination of immunization strategy (with peptide pool), the difference in topology between HLA class I and II molecules and the HLA class I epitope processing mechanism [68] might explain the reasons for the paucity of HLA class I epitopes identified in our study and, thus, revealing to be a caveat for identification of HLA class I restricted epitopes.…”
Section: Discussionsupporting
confidence: 91%
“…HLA‐A2 (HHD) and HLA‐A24 (HHH) transgenic mice (Tgm) were kindly provided by Dr. F.A. Lemonnier . Mice were intradermally injected at the base of the tail with CDCA1‐LP (HLA‐A2 Tgm, 50 µg/mouse; HLA‐A24 Tgm 100 µg/mouse) emulsified in incomplete Freund's adjuvant (IFA) at 7‐day intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Priming of a potent cellular immune response against a human HLA-restricted WNV epitope suggests that H 2 O 2 -WNV-KUNV might stimulate a protective CD8 ϩ T cell response in humans. In support of this, profiling studies from WNV-infected patients have shown that multiple CD8 ϩ T cell epitopes map to the structural proteins of WNV and are presented by different MHC class I alleles (42,54,63,64). Future immunization studies in other HLA transgenic mice and, ultimately, humans will be required to define the extent of antigen-specific CD8 ϩ T cell responses generated after H 2 O 2 -WNV-KUNV administration.…”
Section: Discussionmentioning
confidence: 99%